Creativity: Past, present, and future. Issue 1 (14th November 2018) - Mehta, Ravi; Dahl, Darren W.
Abstract: Our understanding of creativity has come a long way from when it was considered to be a mystical power. Indeed, creativity has grown into a defined cognitive process that can be influenced by a diverse range of internal and external factors. This article begins with a brief discussion of the history of creativity as a psychological construct and then outlines more recent work in the area, particularly focusing on how our understanding of creativity has been expanded in the last decade. In doing so, we explicate four defining factors that have been shown to play a critical role in shaping consumer creativity: cognitive ability, motivation, social‐personality, and environment. The article concludes with a discussion of three topics that we believe hold promise for future research efforts in the area.